Molecular sequence data from populations of Bryoria fuscescens s. lat. in the mountains of central Spain indicates a mismatch between haplotypes and chemotypes. (9th September 2015) - Unknown
Abstract: In order to confirm and investigate the extent of reported mismatches between chemotypes and molecular sequence data in Bryoria fuscescens s. lat., we examined 15 morphologically similar thalli from each of three Pinus forest sites in the Sistema Central of central Spain. Three thalli were rejected due to infections by Phacopsis huuskonenii (not previously published from Spain). The remaining 42 thalli represented nine ITS rDNA haplotypes and four chemotypes (by TLC): fumarprotocetraric and protocetraric acids; norstictic and connorstictic acids; psoromic acid; and fumarprotocetraric, protocetraric and psoromic acids. The molecular phylogenetic tree was characterized by extremely short branch lengths, often only with a single mutational difference, and a single haplotype could have different chemical products. In some cases, adjacent specimens represented different chemotypes, and three thalli appeared to be mixed individuals. Consistency of both molecular and chemical data within individual specimens was demonstrated by examining four different parts of each thallus, which showed only a difference in the location of psoromic acid in some. This is the first population-level study of this taxon, and so it is premature to propose taxonomic changes at this time. Further populations in different parts of the geographical range of this widespread complex now need to be analyzed, and more sensitive chemical analyses conducted, in order to understand the basis of the variability and determine the appropriate taxonomic treatment.